Ethnobotanical Study of Plant Utilization in the Life Cycle Ceremonies of the Kaili Tado Ethnic Group in Central Sulawesi - Syech Zainal; Supriyatman Supriyatman; Aan Febriawan; Amalia Buntu; Muh. Syarif Abd Syukur; Pahriadi Pahriadi; Raya Agni (Biology, Medicine, & Natural Product Chemistry, 2025)
The Kaili Tado ethnic group of Central Sulawesi maintains a rich ethnobotanical tradition in which plants play essential roles in life cycle ceremonies that mark the stages of human existence from birth and marriage to death. This study aimed to identify and analyze the species, uses, symbolic meanings, and conservation status of plants employed in the traditional rituals of the Kaili Tado community. The research was conducted in Langko Village, Lindu District, Sigi Regency, from July to August 2025, using a qualitative descriptive ethnobotanical approach. Data were collected through semi-structured interviews, participatory observation, and field documentation involving twelve key informants, including traditional leaders, ritual practitioners, and elder community members. A total of 11 plant species were recorded, representing diverse functions and cultural symbolism. Plants such as Oryza sativa (rice), Cocos nucifera (coconut), and Areca catechu (areca nut) symbolize prosperity, purity, and strength, respectively, while others like Kalanchoe pinnata and Jatropha curcas serve as protective and purifying agents. Most species are easily available around home gardens, but a few such as Piper betle and Calamus sp. are becoming scarce. The study demonstrates that the Kaili Tado community’s ritual plant use reflects deep ecological awareness and moral philosophy, emphasizing balance between humans and nature. Ethnobotanical documentation of these practices is essential not only for preserving cultural heritage but also for promoting biodiversity conservation and environmental education.